Contributions to the fragmentation of the reason/emotion binomial: (Co)production of an emotionally fel tknowledge - Herrera-Farfan, Nicole (Revista Punto Género, 2023)
This article aims to high light the epistemic value of emotions as data of emotionally felt knowledge in research processes, considering the feminist critique of the pyramidal and power relationship between subject and researcher. Duplicating the purposes to, on the one hand, contribute from the methodological side of qualitative research and, on the other hand, through the form of writing that presents the results. An experience is then presented that combines narrative production with situated and experiential autoethnographic elements in order to expose the (Co)producing that made it posible to obtain knowledge through consensual creation. Emphasising the importance of narrative in orderto explore and understand how the dynamics of male domination experienced in a couple's relationship with a person deprived of liberty are imprinted in a woman's story. The methodological and creative approach is then highlighted as a central part of the theoretical discussion in this article.